2022
DOI: 10.1002/lol2.10302
|View full text |Cite
|
Sign up to set email alerts
|

Drainage‐induced browning causes both loss and change of benthic biodiversity in headwater streams

Abstract: Browning of freshwaters is known to modify food-web structure in lakes via changes to light and nutrient regime. Its effects on biodiversity, particularly in streams and benthic habitats therein, remain largely unknown. We explored the effects of browning on benthic invertebrate biodiversity across a wide gradient of dissolved organic carbon (DOC) concentrations in streams impacted by peatland use. Invertebrate diversity decreased consistently along the gradient whereas community composition exhibited an abrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…These rivers are dark in water color (ranging 110–190 mg L −1 Pt), which is typical for rivers in the study region (Rouvinen, 2010). Increased concentration of DOC can reduce the abundance and biodiversity of zoobenthos communities (Arzel et al, 2020; Brüsecke et al, 2022) but some taxa, such as mayfly Baetis and Chironomidae might even benefit from it (Bellamy et al, 2019; Robbins et al, 2020). The concentration of DOC (especially humic matter) also decreases the pH (Oliver et al, 1983), which has been found to drive the taxonomical diversity of zoobenthos communities, together with nutrient availability (Baker et al, 2022; Heino et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These rivers are dark in water color (ranging 110–190 mg L −1 Pt), which is typical for rivers in the study region (Rouvinen, 2010). Increased concentration of DOC can reduce the abundance and biodiversity of zoobenthos communities (Arzel et al, 2020; Brüsecke et al, 2022) but some taxa, such as mayfly Baetis and Chironomidae might even benefit from it (Bellamy et al, 2019; Robbins et al, 2020). The concentration of DOC (especially humic matter) also decreases the pH (Oliver et al, 1983), which has been found to drive the taxonomical diversity of zoobenthos communities, together with nutrient availability (Baker et al, 2022; Heino et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These rivers are dark in water color (ranging 110-190 mg L À1 Pt), which is typical for rivers in the study region (Rouvinen, 2010). Increased concentration of DOC can reduce the abundance and biodiversity of zoobenthos communities (Arzel et al, 2020;Brüsecke et al, 2022) but some taxa, such as mayfly T A B L E 4 Mean percentage (%) and content (c, μg mg DW À1 ) of essential fatty acids (EFAs), total fatty acid (FA) content (c, μg mg DW À1…”
Section: Zoobenthos Community Structurementioning
confidence: 99%
“…Brownification was also found to decrease macroinvertebrate abundance (Brothers et al, 2014;Arzel et al, 2020;Turunen & Aroviita, 2024), species richness (Brüsecke et al, 2023;Strandberg et al, 2023a), density (Estlander et al, 2010) and habitat use (Horppila et al,2018), while some taxa, such as Chironomidae and Corixidae, became more abundant along the increasing water colour (Wissel et al, 2003;Feuchtmayr et al, 2019). Macroinvertebrates, however, are much less studied than zooplanktons (Figure 2).…”
Section: Overview Of the Findingsmentioning
confidence: 99%
“…Second, the effects of brownification can be species-specific. Within macroinvertebrates, some shredders, such as Asellus aquaticus, were found to respond positively to increasing water colour, while other shredders, such as Ephemerella aroni, responded negatively in Finnish rivers (Brüsecke et al, 2023). Within zooplankton, increasing water colour had positive effects on cladoceran biomass and recruitment, but no effects on copepods (Ekvall & Hansson, 2012;Koizumi et al, 2023).…”
Section: Overview Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation